Solid-Pseudopapillary Tumor of the Pancreas: Our Experience in Bangladesh (Journal of Bangladesh College of Physicians and Surgeons, 2012)
Background: Solid-pseudopapillary tumors of the pancreas (SPTPs) have been reported as rare lesions with “low malignant potential” occurring mainly in young women. This study was designed to understand clinicopathological characteristics of the disease, management strategy and outcome of this rare disease in Bangladesh. Methods: A retrospective review from January 2001 to December 2009 was performed. Clinicopathological, peroperative, postoperative and survival data were obtained from record file. Our cases were discussed in the light of published literature. Results: During this period, 31 patients were diagnosed as having SPTPs (6.9%). Twenty-four (77.4%) females and seven (22.6%) males were identified, with a median age of 24 years (range, 14–44). The median size of the lesions was 7.0 cm (range, 4.8–18). More than 90% presented with vague abdominal pain and lump. Twenty five patients had their primary tumors within the head of pancreas, the rest were in body and tail region. A total of 30 patients presented with local disease and underwent complete resection. One patient was found to have a very large tumor in the head with vascular invasion and underwent debulking of the tumor; which clinically reappear 1 year after debulking but still alive with episodic attacks of abdominal pain. All patients are surviving till date at a follow-up of 2 months to 9 years. Conclusions: SPTP occurs predominantly in women although it can occur in men. Young and middle aged groups are affected. Complete resection or debulking of locally invasive tumor is associated with long-term survival. DOI: http://dx.doi.org/10.3329/jbcps.v29i3.9434 JBCPS 2011; 29(3): 138-142